Peran Pembimbing Kemasyarakatan dalam Penanganan Kasus Narkotika - Suparman S (Madani: Jurnal Ilmiah Multidisiplin, 2023)
As the next generation of the nation, a child creates their own personality based on the environment they live in. The social environment has a powerful influence compared to the family, this social environment can change the child's personality to be bad. An example that can be taken is that drug dealers are targeting children to consume and become drug couriers so that the level of child involvement in consuming and becoming drug couriers is quite high in Indonesia. In a court that involves children, Probation Officers have a significant role and function such as Counselling, Monitoring and Guiding for Children Who Are Faced with the Law according to regulations. The Probation Officer should collect some information about Children Who Are Faced the Law, then in the development or social mentoring, the Probation Officer encourages Children Who Are Faced the Law to be able to return to normal activities without any negative things that can cause the child to fall back into digression. Probation Officers have a function and role which are important for the development of Children Who Are Faced the Law so that they can return to their role as children who are useful for the future.